PERAN ROH KUDUS SEBAGAI PRIBADI KETIGA ALLAH TRITUNGGAL - Enjeli Putri Amisani; Nia Desiska, Oktalia, Sarmauli (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
One thing that is still debated among the Church is regarding one of the Persons of the Trinity, namely the Holy Spirit. The purpose of this writing is to describe the Holy Spirit as the third Person of the Triune God. The research method used is a qualitative research method based on literature and journal analysis. So it is concluded that to understand the divinity of the Holy Spirit, special revelation is needed. Representations of the Holy Spirit illustrate how the Holy Spirit works. The Holy Spirit is God based on his characteristics, plays an important role and has a relationship with the world, plays a role in writing the Bible, and plays a role in the rescue mission with Christ. The holy spirit gives gifts and dwells in the lives of believers.